Predictors of symptom change in the mental health of refugees and asylum seekers (MEHIRA) study examining the effects of a stepped and collaborative care model: a multicentered rater-blinded randomized controlled trial - Kemna, Solveig; Bringmann, Max; Karnouk, Carine; Hoell, Andreas; Tschorn, Mira; Kamp-Becker, Inge; Padberg, Frank; Übleis, Aline; Hasan, Alkomiet; Falkai, Peter; Salize, Hans Joachim; Meyer-Lindenberg, Andreas; et al. (Journal of affective disorders, 2025)
Background - Predictors of symptom improvement are an essential starting point for tailoring psychological treatments to each individual and, in turn, increasing treatment efficacy overall. However, such research regarding refugees/asylum seekers from Arabic-/Farsi-speaking countries is lacking. The current study aimed to characterize predictors for symptom improvement in the Mental Health in Refugees and Asylum Seekers (MEHIRA) study, one of the most extensive multicentered controlled trials on a nationwide stepped and collaborative care model compared to routine German mental health care. - Methods - Variables characterizing symptom change were chosen using backward elimination and inserted into logistic regression models for two depression endpoints, namely the Patient Health Questionnaire-9 (PHQ-9) and the Montgomery Asberg Depression Rating Scale (MADRS). - Results - Six variables were found to be at least marginally significantly associated with symptom decrease in both outcomes: baseline depressive symptom load, comorbid post-traumatic stress disorder, identifying as a refugee, years of schooling, physical health, and post-migration social status difference. Additionally, psychological health and resilience were marginally significant for one of the models. - Limitations - Some predictor constructs - such as social support - were not adequately measured to replicate previous findings. Additionally, the study was underpowered for symptom change prediction of individual treatments beyond the group intervention. - Conclusions - These outcomes indicate that trauma-related elements as well as content on refugee identity and post-migration social status changes should be included in depression interventions for refugees. Further, recommendations for future outcome prediction studies are made.
Online verfügbar: 28. Oktober 2024, Artikelversion: 4. November 2024
Gesehen am 29.04.2025